An institutional logics perspective to evolution of Indian microcredit business models12. (24th August 2018) - Parekh, Nadiya; Ashta, Arvind
Abstract : Institutional development of microcredit in India has been influenced by global pressures, interinstitutional contradictions, and intrainstitutional conflicts in logics. The hybrid model used in India often created dissonance among institutions that operated for a common cause with competing logics. Logics clashed and differences in their legitimacy and sustainability status resulted in mission drift, in favor of the dominant institutional actor. Design issues in social enterprises can result in failed alliances even when a growing market exists and has facilitated experimentation for years.